Review of Technology Adoption Studies in Small and Medium Enterprises (SMEs): A Proposed Theoretical Framework for Malaysian SMEs in the Rural Context - Wong, Vui Chuen; Salmah Topimin (Universal Publishers, 2023)
Purpose: This paper proposes a theoretical framework for Malaysian SMEs in the rural context. It includes the potentially relevant factors from multiple perspectives that may affect SMEs to adopt technologies. Design/methodology/approach: This paper utilizes the narrative literature review method to identify and synthesize the significant factors. This method covered 79 past technology studies in the Malaysian SME field. Findings: The reviewed 79 past studies highlighted multiple perspectives, such as individual, technological, organizational, and environmental, that would be affected Malaysian SMEs to adopt the technology. The 12 significant factors also were identified: performance expectancy, effort expectancy, social influence, compatibility, complexity, perceived risk, top management support, organizational readiness, firm size, government support, competitive pressure, and customer pressure. The unified theory of acceptance and use of technology (UTAUT) and the technology-organization-environment (TOE) framework underpinned the fundamental of the proposed theoretical framework for Malaysian SMEs in the rural context. UTAUT presents the idea of individual perspective, and the TOE framework displays the perspective as it names. Research limitations/implications: The findings of this paper may only provide an applicable guideline from a theoretical perspective. Future studies suggest using a mixed method approach to validate the proposed framework. Practical implications: The findings of this paper provide a literal idea suggesting that the government or the Ministry of Rural Development should consider appropriate guidelines from individual, technological, organizational, and environmental aspects to encourage SMEs operating in rural areas to adopt technologies. Originality/value: This paper addresses the gap by proposing the theoretical framework for Malaysian SMEs in a rural context on technology adoption.